The Translation Procedures of Bible Translation - Ni Wayan Swarniti (RETORIKA: Jurnal Ilmu Bahasa, 2019)
Different procedures of translation are needed to analyze new testament bible of Mark’s gospel. The problems always come if new testament bible of Mark’s gospel from source language unknown in target language conceptly. The data sources of this research were taken from new testament of Mark’s gospel. The technique used in collecting the data was content analysis. The data were analyzed clearly based on the theory of translation procedures by Newmark (1988b). In presenting the data, it was used formal and informal method. According to the results, it can be concluded that found 11 procedures of translation, namely: Transference, Cultural Equivalent, Functional Equivalent, Descriptive Equivalent, Synonymy, Shifts or Transpositions, Modulation, Compensation, Paraphrase, Couplets, and Notes. Based on the results of the analysis, it was not found 4 procedures of translation, namely: Naturalization, Componential Analysis, Through-Translation, and Recognized Translation. The procedures of translation in new testament bible of Mark’s gospel mostly used were shifts or transposition, modulation, and synonymy. The data of shifts or transposition found were 136 of 636 data (21%). It can be concluded that actually holy text often applied shifts or transposition to make the process of translating text easily. In the other word, it was used different form from source text to translate into target text and it was applied also the words in target text that has similar meaning in source text,